2014
DOI: 10.1111/1750-3841.12543
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sulfhydryl Compounds, Carbohydrates, Organic Acids, and Sodium Sulfite on the Formation of Lysinoalanine in Preserved Egg

Abstract: To identify inhibitors for lysinoalanine formation in preserved egg, sulfhydryl compounds (glutathione, L-cysteine), carbohydrates (sucrose, D-glucose, maltose), organic acids (L-ascorbic acid, citric acid, DL-malic acid, lactic acid), and sodium sulfite were individually added at different concentrations to a pickling solution to prepare preserved eggs. Lysinoalanine formation as an index of these 10 substances was determined. Results indicate that glutathione, D-glucose, maltose, L-ascorbic acid, citric acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…It was reported that LAL content of WPC was as high as 145 mg/kg (Friedman, ), which was further increased under processing conditions including heat treatment, sterilization, and alkaline pH. Whey protein contains high level of LAL precursors (such as cystine residues) and the reactants formed by interaction between lysine and dehydroalanine groups (Faist et al, ; Luo et al, ; Rombouts, Lambrecht, Carpentier, & Delcour, ). Increased protein content provided more LAL precursors.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was reported that LAL content of WPC was as high as 145 mg/kg (Friedman, ), which was further increased under processing conditions including heat treatment, sterilization, and alkaline pH. Whey protein contains high level of LAL precursors (such as cystine residues) and the reactants formed by interaction between lysine and dehydroalanine groups (Faist et al, ; Luo et al, ; Rombouts, Lambrecht, Carpentier, & Delcour, ). Increased protein content provided more LAL precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these previous reports, we found that LAL content in the heat treated WPC samples increased by 23% ( p < .05) when the pH was adjusted from 7.5 to 8.5. Formation of LAL is highly dependent on pH value (Friedman, ; Luo et al, ) . Shetty and Kinsella () found that LAL level in yeast proteins formed during a high‐alkali, low‐temperature, and short‐time process (pH 12.5, 65 °C for 2 hr) was seven times greater than the value observed during a low‐alkali, high‐temperature, and long‐time process (pH 10.5, 85 °C for 4 hr).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations